2020
DOI: 10.3389/fimmu.2020.01174
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Derived From Trichinella spiralis Muscle Larvae Ameliorate TNBS-Induced Colitis in Mice

Abstract: Helminths are masters at modulating the host immune response through a wide variety of versatile mechanisms. These complex strategies facilitate parasite survival in the host and can also be exploited to prevent chronic immune disorders by minimizing excessive inflammation. Extracellular vesicles (EVs) are small membrane-bound structures secreted by helminths which mediate immune evasion during parasite infection. The goal of this study was to investigate the immunoregulatory properties of Trichinella spiralis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 43 publications
(48 reference statements)
3
44
0
Order By: Relevance
“…However, the AES are a complex pool of various molecules secreted or excreted by the worms, which are not safe as therapeutic reagents and also not feasible for large-scale production. It is necessary to identify the specific molecules in the ES products involved in immunomodulation (46). LC-MS/MS identified more than 280 protein components in T. spiralis AES with 4 proteins having potential regulatory functions that include cysteine protease inhibitor, serine protease, 53 kDa excretory/secretory antigen, and glutathione-S-transferase (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…However, the AES are a complex pool of various molecules secreted or excreted by the worms, which are not safe as therapeutic reagents and also not feasible for large-scale production. It is necessary to identify the specific molecules in the ES products involved in immunomodulation (46). LC-MS/MS identified more than 280 protein components in T. spiralis AES with 4 proteins having potential regulatory functions that include cysteine protease inhibitor, serine protease, 53 kDa excretory/secretory antigen, and glutathione-S-transferase (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research indicated that NEVs were enriched for secreted membrane-associated proteins, including 14-3-3, and the EVs modulated the in ammatory cytokine expression of BMDMs by triggering TLR2 and MAPK signalling pathways in vitro [8]. Increasing evidence has indicated that EVs are used by parasites to orchestrate bene cial changes in the host environment and to ensure successful infection or activate the innate immune response to control infection [25,26,27]. EVs and their cargo can participate in cell-to-cell communication via various functional biomolecules, including proteins, bioactive lipids, and RNA, which can alter recipient cell functions [28,29,30]; therefore, our previous study also selected NEVs as vaccine controls.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles (EVs) released by parasitic nematodes during infection may provide a powerful strategy for the parasitic nematode to generate widespread effects on host cells ( Coakley et al, 2015 ). Of therapeutic promise, treatment with EVs from T. spiralis and N. brasiliensis suppressed colitis of mice and protection was associated with reduced proinflammatory cytokines and increased Th2 and Treg responses ( Eichenberger et al, 2018 ; Yang et al, 2020 ). In addition to containing lipids and proteins that may be immunomodulatory, EVs may also serve as cargos to deliver small RNAs to host cells, such as macrophages and intestinal cells, where they target and suppress host RNA.…”
Section: Immunomodulatory Moleculesmentioning
confidence: 99%
“…In addition to containing lipids and proteins that may be immunomodulatory, EVs may also serve as cargos to deliver small RNAs to host cells, such as macrophages and intestinal cells, where they target and suppress host RNA. sRNAs have been identified in EVs generated by several parasitic nematodes, including T. spiralis , N. brasiliensis , Trichuris muris , and H. polygyrus , where they are predicted to target host immune gene networks ( Tritten et al, 2017 ; Eichenberger et al, 2018 ; Chow et al, 2019 ; Yang et al, 2020 ). For example, H. polygyrus EVs were able to suppress macrophage responses and IL-33 signaling, and contained miRNAs that specifically targeted host DUSP1 RNA, a regulator of MAPK signaling ( Buck et al, 2014 ; Coakley et al, 2017 ).…”
Section: Immunomodulatory Moleculesmentioning
confidence: 99%